1990
DOI: 10.1002/ana.410280403
|View full text |Cite
|
Sign up to set email alerts
|

Brain microemboli during cardiac surgery or aortography

Abstract: We have observed many focal dilatations or very small aneurysms in terminal arterioles and capillaries of 4 of 5 patients and 6 dogs who had recently undergone cardiopulmonary bypass. A smaller number of sausagelike dilatations distended medium-sized arterioles. Two other patients had a small number of the same microvascular changes following proximal aortography. Thirty-four patients and 6 dogs not undergoing cardiopulmonary bypass had none. (A 35th patient who had not undergone cardiopulmonary bypass or aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
146
0
3

Year Published

1993
1993
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(153 citation statements)
references
References 20 publications
4
146
0
3
Order By: Relevance
“…16,20 The rapid decline in microemboli found in this study is consistent with observations in dogs showing that after CPB, most microvascular occlusions had disappeared within 7 days, 32,33 and with the observations of Blauth et al 34 that vascular occlusions in the retinas of CPB patients were more numerous during CPB than after CPB.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…16,20 The rapid decline in microemboli found in this study is consistent with observations in dogs showing that after CPB, most microvascular occlusions had disappeared within 7 days, 32,33 and with the observations of Blauth et al 34 that vascular occlusions in the retinas of CPB patients were more numerous during CPB than after CPB.…”
Section: Discussionsupporting
confidence: 91%
“…In 7 subjects who had left heart catheterization after CPB (data not shown), we found more microemboli than would be expected from CPB alone. This finding is consistent with the fact that left heart catheterization is known to cause cerebral emboli, 20,56 apparently due to the disruption of aortic and coronary artery atheroma. The disruption of aortic or carotid atheroma may release lipid microemboli as well as larger emboli of atheromatous debris and cholesterol crystals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Digital subtraction angiognaphy of the aortic arch was performed after 10-15 ml of iopamidol R (E. R. Squibb) was injected into each artery for a total of 20 ml at 300 psi. Angiognaphy catheters were used for con- Moody et al [9] observed focal dilatations of small capillanes and arterioles in the brains of patients who had undergone cardiopulmonary bypass. They speculated that these represented gas bubbles or fat emboli.…”
mentioning
confidence: 99%
“…Activation of the complement system with disruption of cell membranes may occur as a result of CPB. , [6][7][8][9][10][11][12][13][14][15][16][17][18][19] In a group of dogs undergoing hypothermic CPB, Johnston et al , 4 found that cerebral blood flow (CBF) was markedly reduced during 150 min of hypothermic CPB and remained so even after rewarming. They saw a small, but significant, rise in intracranial pressure (ICP) but could demonstrate no evidence of brain oedema on the basis of cerebral water content.…”
Section: Discussionmentioning
confidence: 99%